ANALISIS JPZIS NU-CARE LAZISNU JAWA TIMUR TERHADAP PENDISTRIBUSIAN ZAKAT FITRAH DALAM MASJID - Syafiullah, Moh. Rizki; Alamsyah, M. Ghifarri; Rofiqqih, Moh.; Shobah, M. Rajudin; Sa’adah, Mazro’atus (Filantropi : Jurnal Manajemen Zakat dan Wakaf, 2024)
Zakat is a type of philanthropy in the Islamic religion that has a very important role in improving the welfare of the Muslim Ummah and is one of the five pillars of Islam. In terms of zakat management, it is not only the responsibility of the government but there needs to be a role from the community and zakat amil institutions organized by local communities. Especially in terms of Islamic community life, mosques have a very close relationship. Mosques not only function as places of worship but have a very important role in terms of zakat management with models of collecting, distributing, utilizing zakat, and managing human resources for zakat managers. The existence of zakat amil institutions in Indonesia, can help facilitate the process of collecting and distributing zakat in Indonesia. Zakat adalah salah satu filantropi dalam agama Islam yang mempunyai peran yang sangat penting dalam peningkatan kesejahteraan Umat Islam dan merupakan salah satu rukun dari lima rukun Islam. Dalam hal pengelolaan zakat tidak hanya menjadi tanggung jawab pemerintah namun perlu adanya peran dari masyarakat dan lembaga amil zakat yang diselenggarakan oleh masyarakat setempat. Khususnya dalam hal kehidupan masyarakat Islami, masjid mempunyai kaitan yang sangat erat. Masjid tidak hanya berfungsi sebagai tempat ibadah semata, tetapi mempunyai peran yang amat penting dalam hal pengelolaan zakat dengan model pengumpulan, pendistribusian, pendayagunaan zakat dan manajemen sumber daya manusia pengelola zakat. Dengan adanya lembaga-lembaga amil zakat yang ada indonesia dapat membantu memudahkan proses pengumpulan dan penyaluran zakat yang ada di Indonesia.